Interoperasi MARC dan Basis Data Relational - Kusrini Kusrini (Jurusan Teknik Informatika, Fakultas Teknologi Industri, Universitas Islam Indonesia, 2004)
This research intend to communicate relational database model in libraryinformation-system software development with application using data in MARC format. Thewriter has followed the designing, implementation and testing process’ for 2 algorithms to bethe main subject in this paper: MARC-to-Relational and Relational-to-MARC. MARC-to-Relational algorithm is applied when it needed data in MARC format to be processed inrelational model. Conversely, Relational-to-MARC algorithm is applied to publish data fromRelational database model in MARC Format .Keywords: MARC, library, relational database, OPAC.